دراسة مدى تطبيق عناصر منح الائتمان الخمسة ( 5Cs ) في المصارف التجارية في ليبيا (Economic studies journal, 2018)
This study aimed to study the extent to which commercial banks in Libya applied to the elements of granting credit when granting credit, which are (Character, Capacity, Capital, Collateral, and Conditions). The questionnaire was distributed to employees of commercial banks operating in Sirte. The researchers also used simple statistical methods of arithmetic mean, standard deviation, and T test. The study concluded that banks depend on the elements of the borrower's personality, the borrower's ability and the adequacy of the borrower's capital and guarantees But they do not take into account the qualifications of their clients of loan applicants, and they rely more on collateral to avoid risk.